Shifting Cultivation In Various Perspective: Literature Review - Sarlan Adijaya (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Shifting cultivation is a traditional agricultural system practiced for generations in tropical regions of Asia, Africa, and Latin America. Although it supports local livelihoods, it is often debated due to concerns about deforestation, food security, and socio-ecological sustainability. Objectives: This study aims to examine diverse academic perspectives on shifting cultivation and to assess how related discourse has evolved over the past two decades. Methods: A systematic literature review was conducted, focusing on six themes: shifting cultivation as a driver of deforestation; as an adaptive and environmentally friendly system; its role in local food security; its decline under socio-economic pressures; community resistance to negative stigma; and debates in policy and sustainable development. Results: Findings indicate that shifting cultivation is a complex, multidimensional practice shaped by ecological knowledge and cultural identity. Tensions persist between government views that label it destructive and local perspectives that regard it as sustainable. Many studies highlight that misunderstandings arise from oversimplified interpretations that ignore historical and ecological contexts. Conclusion: A holistic, contextual, and evidence-based policy approach is required. Integrating local knowledge with scientific insights is essential to promote fair, adaptive, and sustainable agricultural systems. Such integration will help ensure that policies support ecological resilience, protect cultural traditions, strengthen rural livelihoods, and promote long-term sustainability across diverse landscapes where shifting cultivation continues to play an important role.